School achievement and well-being of immigrant children: the role of acculturation orientations and perceived discrimination - Guerra, R. (2019)
This survey study examined the role of perceived discrimination and acculturation orientations on immigrant children’s achievement and well-being in the school context. Immigrant (n = 229), immigrant descendant (n = 196), and native Portuguese children (n =168) from 4th to 6th grade participated in the study. Results showed the expected gap: immigrant and immigrant descendant children revealed lower school achievement than their native peers; but only immigrant, and not immigrant descendant children, reported lower levels of well-being and peer acceptance. Perceived discrimination was negatively related to school achievement, via an increased desire for culture maintenance, only among immigrant children. The indirect effects of perceived discrimination on well-being and peer acceptance were not significant. However, perceived discrimination was strongly related to lower well-being and acceptance, independently of the target group, suggesting that its negative association with well-being in the school context might encompass a more general process affecting both immigrant and immigrant descendant children.